THE 'FITTED’ MANAGEMENT FOR HUMAN CAPITAL DEVELOPMENT IN PUBLIC SECTOR - Zaiton, A.M.; Kamarul, A.M.; Sihombing, Haeryip; Mohd Yuhasri, Y. (2011)
The success of economic and social development depends on the public sector competency, good governance, and functions. However, the reality in most developing countries which embeds a centralized policy in public services, this becomes a barrier for an effective provision of public services towards global competition. This relates closely to people and organization development in public institutions. The purpose of this paper is to review challenges faced by public sector and to seek solutions based on the concept of integration, implementation, and performance measurement of their business. The proposed conceptual framework is Fitted Management, where the exploration of the organization processing capabilities and how to manage it (to be consistent with the globalization). This will be based on the premise of what constitutes a customer value in the public sector by improving the ability of employees and organizations.